Development Strategy of Masoi (Cryptocarya massoia (Oken) Kosterm.) as Non-Timber Forest Products in Teluk Bintuni, West Papua With SWOT Analysis - Baharinawati, Baharinawati Wilhan Hastanti; Relawan, Relawan Kuswandi; Julanda , Julanda Noya (Jurnal Wasian, 2018)
Non-timber forest products (NTFPs) are forest resources which have comparative advantage and in direct contact with the community. Masoi (Cryptocarya masoia) is one of mainstay Papua NTFPs. This essential oil that produced through bark distillation, used as aromatic raw materials for food, medicines, perfume,s and aromatherapy. The demands of masoi oil are high for domestic and foreign market. This study aimed to formulate development strategy of masoi as non-timber forest products in Teluk Bintuni regency, Papua Barat Province, by identifying external factors (Opportunities, threats) and internal factors (strengths, weaknesses). The research applied SWOT analysis methods by identifying external factors (EFAS) and internal factors (IFAS) as strength, weaknesses, opportunities, and threats. Based on SWOT analysis which conducted by calculate score of external factors and internal factors, the suitable strategy was WO strategy which utilized opportunities to suppress the weaknesses at third quadrant. The third quadrant tended turn around by 1). Socialization and training of masoi cultivation on indigenous people, 2). Legal Counseling to increase legal awareness of the community to overcome land disputes.